My shot : balancing it all and standing tall - Delle Donne, Elena; Durand, Sarah (Simon & Schuster Books for Young Readers, 2018)
Ella Delle Donne, a WNBA MVP and Olympic gold medalist, tells her story of how she gave up a college scholarship offer and chance to play basketball in Connecticut so she could stay in her home state of Delaware to be near her disabled sister, Lizzie. She writes about becoming burned out and leaving the sport of basketball, returning to it later, and overcoming the challenges of competitive sports with hard work and a supportive family.